2022
DOI: 10.3390/foods11091255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Purple Corn Anthocyanin on Growth Performance, Meat Quality, Muscle Antioxidant Status, and Fatty Acid Profiles in Goats

Abstract: This study was conducted to examine the effect of purple corn anthocyanin on performance, meat quality, muscle antioxidant activity, antioxidant gene expression, and fatty acid profiles in goats. The feeding trial period lasted 74 d. The adaptation period was 14 d, and the formal experimental period was 60 d. Eighteen Qianbei-pockmarked goats (Guizhou native goat breed; body weight, 21.38 ± 1.61 kg; mean ± standard deviation) were randomly allotted into three equal groups, including a control with no purple co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…The important indexes for measuring animal growth and slaughtering are dressing percentage and net meat weight. In this study, the dressing percentage of lambs fed diets containing 8%, 16%, and 24% GP was 48.84%, 48.77%, and 49.18%, respectively, which was significantly higher than that of the control and was consistent with the report of Tian et al [23]. However, Yagoubi et al [24] have previously reported that the dressing percentage and net meat percentage of Dorper and Small-Tailed Han F1 hybrid lambs were 49% and 80%, respectively, which were higher than those observed in this work.…”
Section: Effect Of Grape Residue Content On the Meat Productivity And...supporting
confidence: 92%
“…The important indexes for measuring animal growth and slaughtering are dressing percentage and net meat weight. In this study, the dressing percentage of lambs fed diets containing 8%, 16%, and 24% GP was 48.84%, 48.77%, and 49.18%, respectively, which was significantly higher than that of the control and was consistent with the report of Tian et al [23]. However, Yagoubi et al [24] have previously reported that the dressing percentage and net meat percentage of Dorper and Small-Tailed Han F1 hybrid lambs were 49% and 80%, respectively, which were higher than those observed in this work.…”
Section: Effect Of Grape Residue Content On the Meat Productivity And...supporting
confidence: 92%
“…The cultivation of BSF does not require extensive land, significant labor costs, or time investments, making it particularly suitable for development in countries and regions with limited arable land. The Qianbei Ma Goat (the goats raised in the north of Guizhou Province) is known for its excellent meat quality, with mild odor and tender texture [12]. Currently, it is not clear whether BSF has any negative impact on the meat quality of Qianbei Ma goat.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional quality of ruminant meat is mainly determined by its lipid content and fatty acid (FA) composition, as it is the most variable component of meat [ 11 , 12 ]. The improvement in the quality of ruminant meat includes a decrease in saturated fatty acids (SFA) and an increase in monounsaturated and polyunsaturated cis fatty acids (cis-MUFA—PUFA), vaccenic acid (18:1t11), conjugated isomers of linoleic acid (CLA), such as rumenic acid (18:2c9,t11), and decreasing the n-6 PUFA/n-3 PUFA ratio [ 11 , 13 ]. It is noteworthy that 18:2c9,t11 and 18:1t11 are beneficial to consumer health, as they have demonstrated anticarcinogenic activity, and the products from ruminants being the main natural sources of these FAs [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%